Intentions and transitions of inhabitants in Fukushima - Yamaguchi, Sayu; Shinohara, Satoko (International Planning History Society Proceedings, 2018)
The Great East Japan Earthquake was a scale of an earthquake that modern Japan had never experienced before. As a result of this disaster, prolonged evacuation orders were issued to wide areas, and even six years after the earthquake, there are people who still live in temporary houses because they cannot go back to the place where they used to live. This paper focuses on Katsurao Village, Fukushima Prefecture and aims to grasp how the dwellings and family structures changed since the Great East Japan Earthquake as well as the reason for these changes. Intensions as to the future location of their dwellings differ by the age of the members of the household or the areas under the evacuation orders. Young generations do not depend on the existing community, and they wish either to go back to their own old village or move to a more convenient place. It was clarified that many residents want to have a privately-owned house but that there is a small number of people who want to move to a convenient area and choose other types of dwelling.